2019
DOI: 10.1364/oe.27.018706
|View full text |Cite
|
Sign up to set email alerts
|

All optical control of comb-like coherent acoustic phonons in multiple quantum well structures through double-pump-pulse pump-probe experiments

Abstract: We present an advancement in applications of ultrafast optics in picosecond laser ultrasonics -laser-induced comb-like coherent acoustic phonons are optically controlled in a In 0.27 Ga 0.73 As/GaAs multiple quantum well (MQW) structure by a high-speed asynchronous optical sampling (ASOPS) system based on two GHz Yb:KYW lasers. Two successive pulses from the same pump laser are used to excite the MQW structure. The second pump light pulse has a tunable time delay with respect to the first one and can be also t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The bilayer h-BN/MoS 2 geometry used here provides a point of comparison with a similar transduction approach based on spatially-inhomogeneous optical absorption that has been used to generate a broadband frequency comb in GaAs/AlGaAs/InGaAs systems 36 , 37 . A distinct advantage offered by 2D materials is the higher level of spatial confinement, which is illustrated by comparing our 53 nm thick h-BN/MoS 2 stack versus the combined 407 nm thick multiple quantum well structures (plus 3.76 μm for the DBR reflector) in ref.…”
Section: Resultsmentioning
confidence: 99%
“…The bilayer h-BN/MoS 2 geometry used here provides a point of comparison with a similar transduction approach based on spatially-inhomogeneous optical absorption that has been used to generate a broadband frequency comb in GaAs/AlGaAs/InGaAs systems 36 , 37 . A distinct advantage offered by 2D materials is the higher level of spatial confinement, which is illustrated by comparing our 53 nm thick h-BN/MoS 2 stack versus the combined 407 nm thick multiple quantum well structures (plus 3.76 μm for the DBR reflector) in ref.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, our work also covered hybrid structures that consist of QW regions and an underlying superlattice [106,107]. To demonstrate that a free-running dual-comb laser is well-suited for such studies, we prepare an experimental pump-probe setup as shown in Fig.…”
Section: Acoustic Waves In Hybrid Quantum Well/superlattice Structuresmentioning
confidence: 99%